2018
DOI: 10.22271/j.ento.2018.v6.i6.9.01
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of dystocia due to uterine adhesion in a goat

Abstract: Dystocia is defined as difficulty in parturition. It is a common condition in small ruminants especially goats. A four year old Malabari goat was presented to Veterinary Polyclinic, Mannarkkad with the history of full term pregnancy and distention of the ventral abdomen. The animal was showing straining intermittently for the past one day without progressing into parturition. Preliminary examinations followed by pervaginal examination identified the need of cesarean section. The goat was sedated using xylazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Adhesions of the uterus to the abdominal cavity will cause dystocia in the subsequent pregnancy due to insufficient expulsion force. Such cases have to be surgically managed (Khan et al, 2018). Cleaning of the prolapsed uterine mass using normal saline or mild antiseptic solution is necessary to prevent the contamination but aggressive attempts to remove superficial contamination should be avoided since it may cause the absorption of toxic contaminants into the systemic circulation (Scott and Gessert, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Adhesions of the uterus to the abdominal cavity will cause dystocia in the subsequent pregnancy due to insufficient expulsion force. Such cases have to be surgically managed (Khan et al, 2018). Cleaning of the prolapsed uterine mass using normal saline or mild antiseptic solution is necessary to prevent the contamination but aggressive attempts to remove superficial contamination should be avoided since it may cause the absorption of toxic contaminants into the systemic circulation (Scott and Gessert, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It was well-known that the adhesions resulting from hernia, and they are among serosal surfaces due to an imbalance between fibrin deposition and fibrinolysis (Van der Wal and Jeekel, 2007). These adhesions prevent the mobility of uterus within the abdominal cavity resulting in decreased dilatation of cervix and expulsive force at term (Jackson 2004;Purohit, 2006;Erdoğan et al, 2015, Khan et al, 2018. However, this adhesive tissues might be not only the cause of fetal retention, but also had protective effect for maternal toxicities in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly the veterinarian advices administrating antibiotics and hormonal treatment after cesarean section to enhance or accelerate the uterine involution (Đuričić, Valpotić et al, 2016). In obstructive dystocia, special surgical treatment or cesarean section usually is needed, and the cases are accompanied by systemic diseases or shock of the ewes (Khan, Satheesh et al, 2018). Furthermore prolong the second stage of labor, uterine inertia or failure in medical management.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore prolong the second stage of labor, uterine inertia or failure in medical management. Many authors reported that cesarean section was considered an effective way for treatment dystocia in sheep, especially when performed early after the onset of the signs of parturition (Kumar, Talekar et al, 2013, Khan, Satheesh et al, 2018, Bruce, Young et al, 2021. Most research mentioned in this study deals with cases that came to the clinic as emergency conditions and without any information about the past of reproductive history, so the aim of the current study was to analyze and shed light deeper on the main causes of dystocia in ewes.…”
Section: Introductionmentioning
confidence: 99%